Little men - Gibbons, Rodney; Hemingway, Mariel; Sarandon, Chris; Caloz, Michael; Alcott, Louisa May, 1832-1888.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 1998)
Jo, of Little women, and her husband face the threat of foreclosure on their school for boys.
Originally released as a motion picture.
Director of photography, Georges Archambault ; production design, Donna Noonan ; editor, Andre Corriveau ; music, Milan Kymlicka.
Mariel Hemingway, Chris Sarandon, Michael Caloz, Ben Cook.
MPAA rating: PG.
VHS Hi-fi.
Closed-captioned for the hearing impaired.
Keywords: Boarding schools -- Drama; Families -- Drama; Feature films; Films for the hearing impaired